Peran KSH Puspaga dalam Pencegahan Kasus Kenakalan Remaja di Kelurahan Dupak Kota Surabaya - Tesalonika Devvany Nugroho; Nova Dwi Nur Kumala Sari; Diana Claudya Gustafiani; Agnes Monalisa Putri Saluat; Kalvin Edo Wahyudi (IAI Nasional Laa Roiba Bogor, 2024)
Puspaga is a free service from the Surabaya City Government whose task is to prevent early family problems and child delinquency by means of counseling. In carrying out its duties, Puspaga does not handle it independently, but is assisted by various actors including PKBM Volunteers, PPA Task Force in each sub-district. The task force deployed in Dupak Subdistrict is the Great Surabaya Cadre (KSH) which bridges all family and child problems within the subdistrict. This research aims to find out the role of KSH in Dupak Village in preventing cases of juvenile delinquency in Dupak Village, Surabaya City. This research is qualitative research with data collection techniques, namely conducting direct interviews, observation, and documentation of activities. This research uses the theory of the role of government according to Blakely in Mudrajad Kuncoro, which identifies three main roles of government, namely coordinator, facilitator and stimulator. The results of the research show that these three roles have not been implemented optimally in preventing cases of juvenile delinquency in Dupak Village.